Pengaruh Persepsi atas Model Pembelajaran dan Kecerdasan Linguistik terhadap Kemampuan Menuilis Teks Cerpen - Alan Novendra Junaedi; Dendy Sugono (Universitas Indraprasta PGRI, 2022)
The purpose of this study was to analyze the effect of perceptions on learning models and linguistic intelligence on the ability to write short stories. The research method used is a survey research method with multiple regression analysis. The research sample amounted to 50 people. The results of this study illustrate: (1) There is a significant effect of perception on the learning model and linguistic intelligence on the ability to write short stories for state high school students in Sukabumi District. (2) There is a significant influence on the perception of the learning model on the ability to write short stories. (3) There is a significant influence of linguistic intelligence on the ability to write short stories. Keywords: Learning Models, Linguistic Intelligence, Short Stories Text